أثر غياب حس المواطنة في ظهور الجرائم البيئية (Rawafid Journal for Research and Studies, 2019)
يُعد موضوع حماية البيئة، من أكبر التحديات التي تُواجهها البشرية جمعاء، ولعل الهاجس الذي يؤرّق المختصّين هو إيجاد حلول للجرائم البيئية التي يرتكبها الإنسان أو قد يتسبّب في حدوثها. وما دام الأمر كذلك، فإن حماية البيئة لن تتم؛ إلا إذا أدرك الإنسان خطورة ما يفعل وسعى جاهدا للحفاظ على المجال الحيوي المتعدّد الذي يعيش فيه. لذلك تهدف هذه الورقة البحثية، إلى توضيح دور حس المواطنة لدى الفرد للعمل من أجل الحفاظ على حماية البيئة، والعكس صحيح، إذا غاب حس المواطنة انتشرت السلوكات غير الصحية و غير السوية، ومنها ارتكاب الجرائم البيئية بمختلف أنواعها .الكلمات المفتاحية : الجريمة؛ الجرائم البيئية؛ حس المواطنة.Abstract      The issue of protecting the environment is one of the greatest challenges faced by all mankind. Perhaps the concern of specialists is finding solutions to environmental crimes that are committed or caused by humans, and as long as this is the case, the protection of the environment will only take place. Strive to maintain the multi-dynamic space in which he lives. Therefore, this research paper aims to clarify the role of citizenship in the individual to work on the preservation and protection of the environment. Conversely, if the sense of citizenship is absent, the unhealthy and uncoordinated behavior, including the commission of environmental crimes of various kinds will spread.Keywords:  the sense of citizenship; crime; environmental crimes